A case of large sub mitral aneurysm with rheumatic heart disease - Hirachan, Anish; Hirachan, Gopi Prasad; KC, Bishal (Nepalese Heart Journal, 2018)
Sub mitral aneurysm is a very rare cardiac pathology with varied clinical manifestations. The disease process has been postulated to various mechanisms including mainly infection and inflammation. Here, we describe a young female with large submitral aneurysm presenting with rheumatic heart disease in the form of severe mitral regurgitation and aortic regurgitation.